2023
DOI: 10.3390/ijerph20043202
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Adolescent Delinquency: A Theoretically Informed Investigation of Mediators during Middle Childhood

Abstract: Objective: The purposes of this study are twofold. First, we explore the associations between cumulative ACEs at ages 5 and 7 and delinquency at age 14 in a national sample of youth in the United Kingdom (UK). Second, we explore the role of five theoretically relevant mediators in explaining this relationship. Methods: Analyses were based on data from the UK Millennium Cohort Study—a prospective, longitudinal birth-cohort study of more than 18,000 individuals in the United Kingdom. Results: The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Methods: Data from Zambia Violence Against Children and Youth Survey were used (18-24 years old, n=1034. Since 42% of respondents indicated that children needed help with anger management, it can be hypothesised that this anger may stem from ACEs (Jackson et al, 2023). Helping children deal with anger issues will assist in reducing violence in schools.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Methods: Data from Zambia Violence Against Children and Youth Survey were used (18-24 years old, n=1034. Since 42% of respondents indicated that children needed help with anger management, it can be hypothesised that this anger may stem from ACEs (Jackson et al, 2023). Helping children deal with anger issues will assist in reducing violence in schools.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The relationship between childhood adversity and household dysfunction underlies some of the leading causes of death in adults. While prior research focused on specific traumas or parental variables, recent studies integrate multiple adversities, utilizing ACEs factors to assess the effects of exposure to various forms of abuse, neglect, family dysfunction, and household challenges [5,39,46]. Outcomes measured include prevalent health diagnoses, general health assessments (e.g., hypertension), stress-related bodily reactions (e.g., elevated cortisol levels), behavioral issues, cognitive functioning (e.g., growth and learning), and executive functioning aspects (e.g., decision-making, attention, memory, and self-regulation skills).…”
Section: Child Maltreatment and Violencementioning
confidence: 99%
“…Minors are conditioned preliminarily by their families and environment during their socialization process. Juveniles brought up in a chaotic environment may mix with delinquent peers later in their lives [109]. In such a way, juveniles who face ACEs have a greater probability of associating with delinquent peers as a coping mechanism for the trauma [110].…”
Section: Delinquent Peer Association As a Predictor Ofmentioning
confidence: 99%